2022
DOI: 10.5565/rev/catjl.380
|View full text |Cite
|
Sign up to set email alerts
|

Variable First Person Singular Subject Expression in Spoken Valencian Catalan

Abstract: In this paper, I analyze first person singular subject pronoun expression in spoken Valencian Catalan varieties. I present a quantitative and qualitative analysis of 7 interviews from the corpus Parlars, examining 1sg subject rates regarding tense markings (syncretic vs. non-syncretic forms), verb type, and discourse type (monologues vs. conversations). It will be shown that the factor of morphological syncretism as well as verb type influence 1sg subject expression rates. Differently from what has been observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hochberg (1986) investigated how word-final /s/ deletion correlated with subject expression in Puerto Rico Spanish, observing that ambiguity between second-person singular (2sg) and 3sg verb forms, e.g., in the indicative present, or between 1sg, 2sg, and 3sg, e.g., in indicative imperfect correlated with higher subject expression frequencies. More recently, Herbeck (2022) has observed that some Valencian Catalan varieties display high frequency of 1sg subject pronouns in the present perfect, in which the 1sg and 3sg auxiliary has the same form. However, the relevance of the functional hypothesis is not confirmed by some studies with different type of data (Ranson 1991, Cameron 1992, cf.…”
Section: Variable Expression Of Subjects and Objectsmentioning
confidence: 89%
“…Hochberg (1986) investigated how word-final /s/ deletion correlated with subject expression in Puerto Rico Spanish, observing that ambiguity between second-person singular (2sg) and 3sg verb forms, e.g., in the indicative present, or between 1sg, 2sg, and 3sg, e.g., in indicative imperfect correlated with higher subject expression frequencies. More recently, Herbeck (2022) has observed that some Valencian Catalan varieties display high frequency of 1sg subject pronouns in the present perfect, in which the 1sg and 3sg auxiliary has the same form. However, the relevance of the functional hypothesis is not confirmed by some studies with different type of data (Ranson 1991, Cameron 1992, cf.…”
Section: Variable Expression Of Subjects and Objectsmentioning
confidence: 89%